2011
DOI: 10.1016/j.molmed.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Dog models of naturally occurring cancer

Abstract: Studies using dogs provide an ideal solution to the gap in animal models of natural disease and translational medicine. This is evidenced by approximately 400 inherited disorders being characterized in domesticated dogs, most of which are relevant to humans. There are several hundred isolated populations of dogs (breeds) and each has vastly reduced genetic variation compared to humans; this simplifies disease mapping and pharmacogenomics. Dogs age five to eight-fold faster than humans, share environments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
325
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(335 citation statements)
references
References 68 publications
2
325
0
8
Order By: Relevance
“…This suggests that, as some previous studies have suggested, the domestic dog is an ideal model for understanding human cancer (Marconato, Gelain & Comazzi, 2013; Rowell, McCarthy & Alvarez, 2011). However, when we analyzed the specific types of neoplasia associated with death in the two species, we found significant differences.…”
Section: Discussionmentioning
confidence: 63%
“…This suggests that, as some previous studies have suggested, the domestic dog is an ideal model for understanding human cancer (Marconato, Gelain & Comazzi, 2013; Rowell, McCarthy & Alvarez, 2011). However, when we analyzed the specific types of neoplasia associated with death in the two species, we found significant differences.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, germline mutation in the receptor tyrosine kinase MET involved in pathogenesis of canine OSA was identified mainly in Rottweilers (Liao et al 2006). It was shown that besides numerous similarities in tumor biological behavior, parallel genetic features of human and canine osteosarcoma cells also exist (Mueller et al 2007, Rowell et al 2011. So, Rottweilers can be an excellent oncologic animal model for researches on human OSA (Fenger et al 2014, Schiffman andBreen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Growing expectations of breeders and dog owners with regard to diagnosis and treatment encourage scientists to undertake extensive research in this area. Rowell et al (25) report that about 400 diseases in dogs and humans are analogous in the genetic background and course. Certain types of tumours, such as canine mammary carcinoma, are genetically, morphologically, clinically, and prognostically related to human tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Certain types of tumours, such as canine mammary carcinoma, are genetically, morphologically, clinically, and prognostically related to human tumours. Hence, the dog is a suitable animal model for naturally occurring tumours (18,24,25,(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%